Aktiewe gemeente-betrokkenheid by die missionêre diakonaat - 'n ondersoek in 'n gemeente van die NGKA in Mangaung - P. Verster (Acta Theologica)
Research within the community which does not take into account the need and knowledge of the community is not beneficial. Using the notion of the four squares of knowledge, research was conducted in the informal housing community in Mangaung. From the perspective of the congregation of the Christian church, the congregation developed a strategy to get involved in the community. In this way the poor were able to reach out to people in need and seek solutions from within. This has a sound Biblical base.